2005
DOI: 10.1590/s0074-02762005000800007
|View full text |Cite
|
Sign up to set email alerts
|

Shared and non-shared antigens from three different extracts of the metacestode of Echinococcus granulosus

Abstract: Hydatid cyst fluid (HCF), somatic antigens (S-Ag) and excretory-secretory products (ES-Ag [4][5][6][20][21][22][23][24] 52, 80,[100][101][102][103][104] including doublets of 41/45, 54/57, and 65/68 kDa. Non-shared polypeptides of each antigenic extract of E. granulosus were identified, having apparent masses of 108 and 78 kDa for HCF, of 124, 94, 83, and of 89, 66, 42, 39, 37,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus far, the use of these antigens is predominantly restricted to scientific applications, and neither is available for general use (5). The number of reports on the use of protoscolex as an antigen for detecting antibodies in human hydatidosis is limited (16)(17)(18)(19). Chemale et al (20) described the analysis of E. granulosus metacestode protein extract by 2-DE and the identification of prominent proteins by peptide mass fingerprinting (PMF).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the use of these antigens is predominantly restricted to scientific applications, and neither is available for general use (5). The number of reports on the use of protoscolex as an antigen for detecting antibodies in human hydatidosis is limited (16)(17)(18)(19). Chemale et al (20) described the analysis of E. granulosus metacestode protein extract by 2-DE and the identification of prominent proteins by peptide mass fingerprinting (PMF).…”
Section: Discussionmentioning
confidence: 99%
“…In E. granulosus protoscolex ESP, two new E. granulosus antigens of 89 kDa and 74 kDa have been proposed as potential diagnostic molecules for the immunodiagnosis of human CE [65]. Subsequent cross‐reactivity studies by immunoblot and ELISA inhibition demonstrated that E. granulosus protoscolex ESPs share a high proportion of antigenic components with protoscolex somatic extracts and, to a lesser extent, with hydatid fluid [66].…”
Section: Antigens For the Immunodiagnosis Of Aementioning
confidence: 99%
“…Also, variation in mean OD values within the infected groups may be related to different sensitivity of each Ag as well as the specific level Abs titer in their sera. Few studies used soluble protoscolices antigen in diagnosing human echinococcosis (Carmena et al, 2004), but many proteins of E. granulosus as hydatid fluid & protoscolices were immunogenic and used to diagnose specific Abs in dogs and intermediate host as sheep (Carmena et al, 2005). Fotoohi et al (2013) reported the suitability of HC Ag of sheep origin to diagnose infection in patients.…”
Section: Discussionmentioning
confidence: 99%